Recombinant ecology -- a hybrid future? - Rotherham, Ian D. (Springer, 2017)
This book addresses critical issues of changing ecology and ecosystems consequent on urbanisation, globalisation, climate change, and human cultural influences. Human-induced and natural climate changes and globalisation accelerate hybridisation; anthropogenic influences causing disturbance, nutrient enrichment, habitat replacement (formation and destruction), and global dispersal of species. The ecological processes driving changes are natural mechanisms of ecological successions and changes, and of species and ecosystem hybridisation or adaptation. Today species mix at rates unprecedented in biodiversity evolution history; with the Anthropocene, the latest great evolutionary epoch, nature adapts to a new canvas and changed template. The dramatic and largely unrecognised consequence is hybridisation of both species and ecology. Whilst this process is most easily observed and recognised in increasing urban environments, it occurs more widely, in forestry and agricultural landscapes. With new environmental conditions forged plants, animals and fungi move and mix, beyond natural distributions and limits; old and new, native and exotic, enmeshed in recombinant communities and hybrid ecosystems. Here, and especially in the rapidly expanding urban heartlands of this new ecology, native and alien jostle for position forming novel interactions and dependencies. This challenging new approach to understanding ecological systems especially in urban and urbanised areas synthesises current ideas. The book develops an historic context to ecological fusion and recombinant or hybrid ecosystems. Invasive and non-native or alien species spread, often aggressively around the globe. Current thinking in ecology and nature conservation fails to accommodate the consequences of changing environmental conditions and fusion of species and ecological communities. Urbanisation and globalisation combine with climate and other changes to trigger new hybrid communities and ecologies. Embedding this approach into current ecological thinking this book presents an overview of ideas set in the exemplar case study area of the British Isles. However, the approaches, ideas and conclusions will find application in ecosystem studies and in nature conservation around the world.
Keywords: Ecology.; Invasive plants.; Introduced organisms.; elektronické knihy; electronic books